You deserve what you eat: lessons learned from the study of the melanin-concentrating hormone (MCH)-deficient mice. Issue 12 (21st October 2010) - Wang, Yan; Ziogas, Dimitrios C; Biddinger, Sudha; Kokkotou, Efi
Abstract : Objectives: Diet plays a crucial role in the development of obesity and insulin resistance via multiple mechanisms. Saturated fatty acids can directly trigger tissue specific proinflammatory pathways via Toll-like receptor-4 (TLR4)-dependent mechanisms. Moreover, diet can change the gut microbiome and increase gut permeability. However, very few studies have addressed the obesity-independent role of diet. Dissecting the effects of diet from those of obesity per se will enhance our understanding of the underlying pathogenesis, and, at the translational level, advance our treatment approaches for obesity and its co-morbidities. Methods: Melanin-concentrating hormone (MCH) is an important regulator of appetite and energy balance. MCH-deficient mice are resistant to diet-induced obesity, primarily due to increased locomotor activity. We took advantage of the unique phenotype of these mice to examine the metabolic and inflammatory consequences of a 15-week consumption of a diet high in saturated fat. Results: MCH-deficient mice chronically exposed to a high-fat diet gain less weight compared to their wild-type littermates, despite similar food intake, and are protected from hepatosteatosis. They also lack obesity-associated upregulation of serum leptin and insulin levels and have improved total body insulin sensitivity. Nevertheless, we found indistinguishable liver-specific innate immune responses in both genotypes associated with high-fat feeding, which involved activation of TLR4 and its downstream effectors, MyD88, p38 MAP kinase and STAT-3. Conclusions: Our findings indicate that high-fat feeding is deleterious to the liver, independently of the obesity status. They also suggest that MCH is not necessary for the TLR4-dependent immune response triggered by the high-fat diet.